2017
DOI: 10.1002/hup.2583
|View full text |Cite
|
Sign up to set email alerts
|

Cilostazol adjunctive therapy in treatment of negative symptoms in chronic schizophrenia: Randomized, double-blind, placebo-controlled study

Abstract: An 8-week course of treatment with cilostazol as an adjunct to risperidone showed a favorable safety and efficacy profile in patients with schizophrenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 30 publications
2
11
0
Order By: Relevance
“…Similarly, roflumilast, which is also a PDE4 inhibitor, is nowadays a treatment for chronic obstructive pulmonary disease and was suggested as a cognitive enhancer in schizophrenia through enhancing the amplitude of mismatch negativity, working memory‐related theta oscillations, and verbal memory with normalization deficits in attentional set‐shifting and learning‐related activity impairments by increasing intracellular cAMP in brain areas implicated in cognitive deficits in patients with schizophrenia 41–43 . Moreover, our findings were in agreement with a former study reported that cilostazol, PDE3 inhibitor, has improved the negative symptoms in schizophrenia patients in an 8‐week treatment study as an adjunct to risperidone 44 . Furthermore, inhibition of PDE1 by DSR‐141562 in an animal model exhibits potent efficacy for positive, negative, and cognitive symptoms associated with schizophrenia via augmentation of D1 receptor signaling 45 …”
Section: Discussionsupporting
confidence: 92%
“…Similarly, roflumilast, which is also a PDE4 inhibitor, is nowadays a treatment for chronic obstructive pulmonary disease and was suggested as a cognitive enhancer in schizophrenia through enhancing the amplitude of mismatch negativity, working memory‐related theta oscillations, and verbal memory with normalization deficits in attentional set‐shifting and learning‐related activity impairments by increasing intracellular cAMP in brain areas implicated in cognitive deficits in patients with schizophrenia 41–43 . Moreover, our findings were in agreement with a former study reported that cilostazol, PDE3 inhibitor, has improved the negative symptoms in schizophrenia patients in an 8‐week treatment study as an adjunct to risperidone 44 . Furthermore, inhibition of PDE1 by DSR‐141562 in an animal model exhibits potent efficacy for positive, negative, and cognitive symptoms associated with schizophrenia via augmentation of D1 receptor signaling 45 …”
Section: Discussionsupporting
confidence: 92%
“…Naturally, the used triple application L-NAME–L-arginine–combined L-NAME and L-arginine and stable gastric pentadecapeptide BPC 157 administration also would need the fMRI and EEG modalities to measure the functional connectivity (i.e., temporal cross-correlations) between brain regions will be preferable to support and understand the presented results in future experiments. Further, atypical antipsychotics [ 50 , 51 , 52 ], NMDAR indirect agonists [ 53 ], NMDAR-glycine site agonists [ 54 ] studied in clinical trials for schizophrenia and large list of adjunctive agents with so far little advantage from different classes (i.e., antidepressants [ 55 ], psychostimulants [ 56 ], anxiolytics [ 57 ], anticonvulsants [ 58 ], muscarinic receptor agonists and peripehral antagonists [ 59 ], selective inhibitor or phosphodiesterase III [ 60 ], statins [ 61 ]) might also benefit from the studies of the NO-agents triple application and NO-specific therapy relation. Likewise, sampling and analysis of the dopamine, the synaptic/or extra-synaptic GABA, glutamate levels for different brain regions/neuronal circuits during treatments will be helpful.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the 17-item HDRS was used at baseline and week 8 to quantify depressive symptoms and their changes over the trial period ( Hamilton, 1960 ). Both scales have been widely employed in previous clinical trials of schizophrenia in the Iranian population ( Iranpour et al, 2016 ; Rezaei et al, 2017 ; Ghajar et al, 2018a ).…”
Section: Methodsmentioning
confidence: 99%
“…ESRS can measure all drug-induced movement disorders irrespective of changes in psychopathology as measured by the PANSS ( Chouinard and Margolese, 2005 ). The ESRS was previously applied in Iranian clinical trials demonstrating valid results ( Iranpour et al, 2016 ; Rezaei et al, 2017 ; Ghajar et al, 2018a ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation